Adolescent Pregnancy: Assessing Familism with Bardis Scale (2019)
Introduction: Familism is a multidimensional cultural construction that gives importance to family ties. Study was done to estimate prevalence of familism and its link to psychosocial variables in pregnant adolescents who received prenatal care. Material and Methods: A cross-sectional study that is part of the project “Gestación” was carried out. Four hundred and ninety-nine pregnant adolescents received obstetric care, completed sociodemographic characteristics forms and answered scales of religiosity, spirituality, family function, happiness, resilience and familism based on the Bardis scale in Cartagena, Colombia. Correlation was established among familism, sociodemographic and psychosocial variables. Multiple linear regressions were made to identify associated variables; p<0.05 was significant. Results: the average age was 17 years old. 41% of participants strongly agreed to give their parents their earnings, 84% obeyed siblings, 65% thought family is more important than personal interests, 75% defended family, 87% are loyal to family, 90% help their parents, 75% help their uncles, 74% help their parents in-law and 66% live with other relatives. There were significant factors related to greater familism: a higher level of resilience, sexual partner with secondary studies, having a functional family and three or more ultrasounds p<0.05. Primary studies, not attending church, having a dysfunctional family and poor resilience were negative predictors of familism p<0,001. There was significant positive correlation between spirituality and happiness with familism. Conclusions: a high level of familism was observed in a group of pregnant adolescents. We recommend that healthcare professionals explore psychosocial aspects of teenage pregnancy to promote coping strategies regarding motherhood responsibilities.